Prevalence and associated factors of diarrhea among under-five children in the Jawi district, Awi Zone Ethiopia, 2019. Community based comparative cross-sectional study - Gessesse, Dereje Nibret; Tarekegn, Abebe Aynalem (Frontiers in Pediatrics, 2022)
Introduction Although most deaths are preventable with simple and inexpensive measures, death from diarrhea accounts for one out of nine deaths in children worldwide which makes it the disease with the highest mortality rate in children under the age of five. Therefore, this study is aims to investigate diarrhea prevalence and risk factors among children under the age of five in Jawi district, Awi Zone, Ethiopia. Materials and methods A comparative cross-sectional study was done among 440 study participants from March to June 2019. Data were collected with a face-to-face interviewer-administered questionnaire. Data was entered into EPI Info version 7 software and cleaned and analyzed using SPSS version 20 software. Binary logistic regression was done to assess independent factors associated with the dependent variable. A significant association was determined using an adjusted odds ratio at a confidence level of 95% and a p-value of less than or equal to 0.05. Results In the current study, the overall under-five children diarrheal disease was found to be 15.5%. Diarrheal disease prevalence in model and non-model households was 10.9 and 20%, respectively. Shallow water [AOR: 6.12, 95%CI; (1.52, 24.58)], and maternal diarrhea [AOR: 4.11, 95%CI; (1.75, 9.61)] were determinants of childhood diarrhea. Place of birth [OR: 2.52, 95%CI (1.16, 5.49)] and maternal diarrhea [AOR: 3.50; 95%CI (1.28, 9.56)] in non-model households were also determinants of childhood diarrhea. Conclusion Under-five children diarrheal disease was found to be high in the Jawi District. Thus, to decrease the disease prevalence in the study area, the health extension workers aim to better educate the mothers on how to handle diarrheal diseases. It is also better for concerned stakeholders to promote institutional delivery and to give access to safe water for the community.